Women in healthcare experiencing occupational stress and burnout during COVID-19: a rapid review. Issue 4 (8th April 2021) - Sriharan, Abi; Ratnapalan, Savithiri; Tricco, Andrea C; Lupea, Doina
Abstract : Context: COVID-19 has had an unprecedent impact on physicians, nurses and other health professionals around the world, and a serious healthcare burnout crisis is emerging as a result of this pandemic. Objectives: We aim to identify the causes of occupational stress and burnout in women in medicine, nursing and other health professions during the COVID-19 pandemic and interventions that can support female health professionals deal with this crisis through a rapid review. Methods: We searched MEDLINE, Embase, CINAHL, PsycINFO and ERIC from December 2019 to 30 September 2020. The review protocol was registered in PROSPERO and is available online. We selected all empirical studies that discussed stress and burnout in women healthcare workers during the COVID-19 pandemic. Results: The literature search identified 6148 citations. A review of abstracts led to the retrieval of 721 full-text articles for assessment, of which 47 articles were included for review. Our findings show that concerns of safety (65%), staff and resource adequacy (43%), workload and compensation (37%) and job roles and security (41%) appeared as common triggers of stress in the literature. Conclusions and relevance: The current literature primarily focuses on self-focused initiatives such as wellness activities, coping strategies, reliance of family, friends and work colleagues to organisational-led initiatives such as access to psychological support and training. Very limited evidence exists about the organisational interventions such as work modification, financial security and systems improvement.